Echinoderms Community Structure In Pegametan Bay, Buleleng, Bali - Arya Maulana Rabani; Dewa Ayu Angga Pebriani; I Ketut Wija Negara (Advances in Tropical Biodiversity and Environmental Sciences, 2024)
Echinoderms are key ecological organisms that play a protective role in balancing the marine ecosystem by breaking down trash or leftover organic material that is not used by other species. Echinoderms are marine biota that are sensitive to changes in water characteristics, so they can be used as bioindicators. Echinoderm habitats can be found in all marine ecosystems, but the highest diversity is found in intertidal areas, which are easily affected by land activity. One of the intertidal areas that is often used by humans is the Bay Area. This research aims to find out the types of echinoderms and analyze the community structure of echinoderms in Pegametan Bay, Bali. The research was carried out using the method of line transect at 18 points for data on the number and types of echinoderms in depth 1x1 m quadrat transect. Based on the observations, it was found that there are 3 classes of echinoderms that live on Bingin Beach (Echinoidea, Asteroidea, and Holothuroidea) with 3 orders, namely Diadematoida, Valvatida, and Holothuriida. The most commonly found species is D. setosum from the Echinoidea class. The structure of the echinoderm community in Pegametan Bay is shown by an average density value of 12.60 ind/m² with a diversity index value of 0.46, which is classified as low diversity; a uniformity index value of 0.36, which is relatively low; and a dominance index of 0.73, which is relatively high. Based on the results obtained, it can be concluded that the diversity index in Pegametan Bay is low, the evenness index is relatively low, and the dominance index is high. The values of temperature, pH, dissolved oxygen (DO), and salinity are still within the standard limits for marine biota.